¡TIC, TOC, TAC, AI! : Arte Sonoro, Tecnología y Ciudad en el s.XXI. (REVISTA NODO, 2021)
Different works and projects related to sound art, the city and the use of contemporary technologies are shown. It is divided into introduction, methodology, results and conclusions. The results first point out well-known works that serve as antecedents to the following projects showing the traditional meeting of this genre with technology. Afterwards, the core works of the text are addressed, advancing from the Internet and the Information and Communication Technologies, to Geographic Information Systems, Apps, Virtual Reality, Artificial Intelligence, Big Data and the Internet of Things. With all this it is shown that these technologies offer important possibilities to sound art, the city and citizens, that this genre continues to benefit from technological innovations and that certain themes and praxis such as maps, cartographies, audioguides, city concerts or the city as an instrument continue directly or indirectly taking new levels of depth today.